Targeting oxidant-dependent mechanisms for the treatment of COPD and its comorbidities - Iván Bernardo; Steven Bozinovski; Ross Vlahos (2015)
Chronic obstructive pulmonary disease (COPD) is an incurable global health burden and is characterised by progressive airflow limitation and loss of lung function. In addition to the pulmonary impact of the disease, COPD patients often develop comorbid diseases such as cardiovascular disease, skeletal muscle wasting, lung cancer and osteoporosis. One key feature of COPD, yet often underappreciated, is the contribution of oxidative stress in the onset and development of the disease. Patients experience an increased burden of oxidative stress due to the combined effects of excess reactive oxygen species (ROS) and nitrogen species (RNS) generation, antioxidant depletion and reduced antioxidant enzyme activity. Currently, there is a lack of effective treatments for COPD, and an even greater lack of research regarding interventions that treat both COPD and its comorbidities. Due to the involvement of oxidative stress in the pathogenesis of COPD and many of its comorbidities, a unique therapeutic opportunity arises where the treatment of a multitude of diseases may be possible with only one therapeutic target. In this review, oxidative stress and the roles of ROS/RNS in the context of COPD and comorbid cardiovascular disease, skeletal muscle wasting, lung cancer, and osteoporosis are discussed and the potential for therapeutic benefit of anti-oxidative treatment in these conditions is outlined. Because of the unique interplay between oxidative stress and these diseases, oxidative stress represents a novel target for the treatment of COPD and its comorbidities.